(3GdGOGQI GdeMdjI (B/s - (3TWfGhj, Ydj NWGQs ((3YeGf(B: s (3OGQ hGFd(B, s, 2002)
(3JMOjO eG gjI GdJfXje GdeQcRj(B-(3JMOjO eGgjI GdeQcRjI GdGOGQjI(B-(3YfGUQ GdGOGQI GdeQcRjI aj GdCQOf(B-(3GddGeQcRjI GdGbdjejI(B-(3GdCSGS GdbGfhfj ddfXGe GddGeQcRj GdEbdjej(B-(3JWHjbGJ GdfXGe GddGeQcRj GdEbdjej aj GdCQOfs
Keywords: (3GdEOGQI(B- (3GdCQOfs